Surgical Safety Checklist Popularity among the surgeons?A survey - Malhotra, Mohinder Kumar; Malhotra, Suchitra; Chowdhary, Kunal; Khera, Aadhar; Singh, Puneet (Bangladesh Journal of Medical Science, 2017)
Background: W.H.O has introduced a surgical safety checklist as part of its Safe Surgery Saves Lives initiative. The checklists purpose was to reduce surgical complications that resulted from inadequate safety practices and promote greater communication among surgery teams. It is made necessary to use the surgical safety checklist in the operation theatres across the world but is it really used in the actual practical setup? Material & Methods: With that idea in mind we had conducted a study to know about the awareness and practical use of surgical safety checklist among surgeons attending Haryana Chapter of Association of Surgeons in India Conference (HASICON) 2014 in there surgical practice. Printed performa with a set of questions was given to the delegates and the result was analysed. Result: Only 57% of the study group had heard about the safety checklist and only 32% of them are using it in their surgical practice. Conclusion: There is an urgent need to spread awareness about the safety checklist and one way of achieving it is by demonstration papers in conferences across the world. Bangladesh Journal of Medical Science Vol.16(4) 2017 p.521-524